A charity by any other name : submission to the Board of Taxation on the draft Charities Bill, 2003 (ACOSS info, 2003)
Includes: Advocacy by charities. Australian Tax Office (ATO). Charity law reform. Public Benevolent Institution (PBI). Fringe Benefits Tax. Charity Definitions Inquiry. Federal Charity Commission. Amendments to the draft Charity Bill. Charity Definition Inquiry. Defining and regulating advocacy.